Design of Business Model Canvas For Investment Planning In Biotechnology: The Business Case For Halal Detection Kit Production - Arief Muhammad Sigit; Dominicus Savio Priyarsono; Siti Jahroh (Asian Journal of Social and Humanities, 2025)
This research aims to develop a new business model canvas to support PT XYZ's strategic plan in planning investment in the production of halal detection kits based on real-time PCR. The nine blocks of the business model canvas are used as a framework to evaluate the running business model, identify market opportunities, and design a business model that can optimize the potential of the halal market in Indonesia, which continues to grow. The results show that the optimization of elements, such as value proposition, key activities, key resources, customer relationships, cost structure, and revenue streams can support PT XYZ's transformation from distributor to manufacturer. The development of this new business model is expected to improve operational efficiency, maximize the potential of the local market, and create innovative and sustainable products. This research provides a strategic foundation for companies to take advantage of opportunities in the halal industry while increasing competitiveness through collaboration and adoption of modern technology in supporting value-based business development for the halal industry.